HELENA: An intelligent digital assistant based on a Lifelong Health User Model. Issue 1 (January 2023) - Polignano, Marco; Lops, Pasquale; de Gemmis, Marco; Semeraro, Giovanni
Abstract: Digital Assistants are overgrowing in the mobile application industry and are now implemented in various commercial devices. So far, their use in the health domain is limited and often narrowed to remote monitoring of specific patient pathology. The main contribution of this paper is HELENA, a conversational agent endowed with healthcare knowledge that supports users in managing their lifelong health user model (LHUM) by providing simple services. The proposed platform has been evaluated in a user study involving 160 participants who gave feedback on the digital assistant and the profile conceptualization. The results showed that LHUM is comprehensive and inclusive (76.25% positive feedback), and the users appreciated that all personal health data were available in one single profile (83.75% positive feedback). Furthermore, the user interaction was pleasant, functional, and efficient. Also, measurement management, data sharing, and food diary management have been broadly appreciated. The outcomes of our investigation suggest that adopting a lifelong comprehensive user profile by digital assistants is a promising research direction. Highlights: Definition of a lifelong health user model. Definition of an intelligent digital assistant, HELENA. Evaluation through a large user study to evaluate the model and the digital assistant.